Emma ebook - Austen, Jane (Duke Classics, 2012)
Emma stands a little apart from Jane Austen's other novels. It is perhaps the most self-aware, socially critical and ironic of all her works. Her protagonist, Emma Woodhouse, is a beautiful, rich girl who is also spoiled, proud and blinded by her own situation in life. She begins to understand herself and life a little better when her romantic schemes - charitable good works to those around her - become entangled in tensions of class and of the heart. Austen wrote of Emma, "I am going to take a heroine whom no-one but myself will much like."